2021
DOI: 10.3389/fimmu.2021.716819
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Mellitus and Latent Tuberculosis Infection Moderately Influence Innate Lymphoid Cell Immune Responses in Uganda

Abstract: BackgroundType 2 diabetes mellitus (T2DM) is a major risk factor for the acquisition of latent tuberculosis (TB) infection (LTBI) and development of active tuberculosis (ATB), although the immunological basis for this susceptibility remains poorly characterised. Innate lymphoid cells (ILCs) immune responses to TB infection in T2DM comorbidity is anticipated to be reduced. We compared ILC responses (frequency and cytokine production) among adult patients with LTBI and T2DM to patients (13) with LTBI only (14), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 79 publications
1
9
0
Order By: Relevance
“…In accordance with the findings in previous studies [9,36], this study revealed significantly lower plasma levels of TNF-α and IL-17 in DM patients with LTBI than non-LTBI counterparts, suggesting increased TB susceptibility through the decreasing phagocytic ability of macrophages, interference with granuloma formation [37] and inhibiting Mtb-specific memory responses [38]. We though herein demonstrated the significant correlation between Th1-and Th17-related cytokines and the 6 most differentially abundant taxa of gut microbiota, further studies should be conducted to explore the immunomodulatory effect of gut microbiome on Mtb infection.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with the findings in previous studies [9,36], this study revealed significantly lower plasma levels of TNF-α and IL-17 in DM patients with LTBI than non-LTBI counterparts, suggesting increased TB susceptibility through the decreasing phagocytic ability of macrophages, interference with granuloma formation [37] and inhibiting Mtb-specific memory responses [38]. We though herein demonstrated the significant correlation between Th1-and Th17-related cytokines and the 6 most differentially abundant taxa of gut microbiota, further studies should be conducted to explore the immunomodulatory effect of gut microbiome on Mtb infection.…”
Section: Discussionsupporting
confidence: 93%
“…26 Conversely, type 2 diabetes patients infected with tuberculosis exhibited an obvious reduction in circulating ILC3s relative to those without diabetes. 27 Additionally, ILC3s have been shown to participate in the progression of other metabolic diseases, such as fatty liver disease. 28 Despite the increased levels of circulating ILC3s in HUA patients observed in this study, whether or not ILC3s contribute to HUA development requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It indicated participants with C-TST conversion in the baseline IGRA-negative group are more inclined to the true LTBI status. T2DM patients may have a false-negative TST or C-TST due to immunosuppression ( 12 , 33 ). However, the use of the booster effect to increase the detection of LTBI had been recommended in different populations, including immunosuppressed patients as well as healthy population ( 34 – 36 ).…”
Section: Discussionmentioning
confidence: 99%